TECHNIQUES TO SOLVE UNIFORM THIRD DEGREE EQUATION HAVING FOUR VARIABLES - Nagarajan, Thiruniraiselvi; Mayilrangam, Gopalan (International Journal of Research -GRANTHAALAYAH, 2024)
Each article should be accompanied by an abstract of up to 250 words in English, which should mention all the principal facts and conclusions set forth in the paper. A similar abstract in Hindi language may be added, but this is not required. The homogeneous cubic equation with four unknowns given by is studied for obtaining its non-zero distinct integer solutions. Substitution technique and factorization method are utilized to determine the same.